Tandem diazotization/cyclization approach for the synthesis of a fused 1,2,3-triazinone-furazan/furoxan heterocyclic system - Sidunets, Yuri A.; Melekhina, Valeriya G.; Fershtat, Leonid L. (Beilstein Journal of Organic Chemistry, 2024)
A straightforward protocol for the synthesis of a previously unknown [1,2,5]oxadiazolo[3,4-d][1,2,3]triazin-7(6H)-one heterocyclic system was developed. The described approach is based on tandem diazotization/azo coupling reactions of (1,2,5-oxadiazolyl)carboxamide derivatives bearing both aromatic and aliphatic substituents. The NO-donor ability of the synthesized furoxano[3,4-d][1,2,3]triazin-7(6H)-ones was additionally evaluated. The elaborated method provides access to novel nitrogen heterocyclic compounds with potential applications as drug candidates or thermostable components of functional organic materials.
Keywords: molecular hybridization; nitric oxide; nitrogen heterocycles; 1,2,5-oxadiazoles; 1,2,3-triazin-4-one